2009
DOI: 10.1021/ma801504e
|View full text |Cite
|
Sign up to set email alerts
|

Donor−Acceptor Poly(thiophene-block-perylene diimide) Copolymers: Synthesis and Solar Cell Fabrication

Abstract: Donor-acceptor diblock copolymers, composed of regioregular poly(3-hexylthiophene) (rrP3HT) as the electron donor block and poly(perylene diimide acrylate) (PPDA) as the electron acceptor block, were prepared and used to fabricate a solar cell. Vinyl-terminated rrP3HT was synthesized by Grignard metathesis polymerization and converted to an alkoxyamine macroinitiator. This polythiophene macroinitiator was used in controlled free radical polymerization of a perylene diimide-containing acrylate. The targeted don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
234
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(238 citation statements)
references
References 26 publications
3
234
0
1
Order By: Relevance
“…130,131 Emrick and coworkers also visited P3HT-perylene bisimide diblock copolymers. 132 A typical example of the use of BCPs in the active layer of OPVs can be found in the work of Tajima and coworkers. They developed a Diblock copolymers of P3HT with one block having pendant fullerene [ Fig.…”
Section: Reviewmentioning
confidence: 99%
“…130,131 Emrick and coworkers also visited P3HT-perylene bisimide diblock copolymers. 132 A typical example of the use of BCPs in the active layer of OPVs can be found in the work of Tajima and coworkers. They developed a Diblock copolymers of P3HT with one block having pendant fullerene [ Fig.…”
Section: Reviewmentioning
confidence: 99%
“…It is, therefore, essential to postprocess after deposition of the block copolymer thin film, as shown in Figure 20, where solvent annealing was used to order the block copolymer. 143 Mü ller et al 206 synthesized a diblock copolymer of poly(3-hexylthiophene)-block-polyethylene (P3HT-b-PE) and observed that this system has good conductive properties alongside mechanical toughness, both qualities that are desirable for flexible solar cells. Although not strictly concerned with making OPVs from this material, it shows the possibilities of a double crystalline diblock system.…”
Section: Processingmentioning
confidence: 99%
“…7(f)], 180 and of Russell and Emrick [ Fig. 7(h)] 143 but with different chain-ends and linking groups. They found that the higher molecular weight polymer had improved charge transport properties, which they correlated with increases in the hole carrier mobility due to an increase in crystallite domain sizes.…”
Section: Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts have been carried out in order to obtain ideal morphology and high device performance. For example, poly(3-alkylthiophene) based block copolymers containing a polyacrylate block with perylene bisimide pendant groups were investigated [12,13]. However conversion efficiencies were still lower than that of the conventional P3HT/PCBM composite indicating that further investigations, including molecular design and process for film fabrication, are required for improving performance.…”
Section: Introductionmentioning
confidence: 99%